Insoles Treated with Bacteria-Killing Nanotechnology Bio-Kil Reduce Bacterial Burden in Diabetic Patients and Healthy Controls - Difei Lu; Xiaohui Guo; Yun Li; Bo Zheng; Junqing Zhang (Journal of Diabetes Research)
Our study investigated the effectiveness of bacteria-killing nanotechnology Bio-Kil socks on bacterial burden reduction in diabetic patients and healthy individuals. Four strains of S. aureus and four strains of E. coli were cultured and dropped on Bio-Kil socks and control socks for 0 h, 8 h, and 48 h of incubation. Diluted samples were inoculated and bacterial counts were recorded. Additionally, 31 patients with type 2 diabetes and 31 healthy controls were assigned to wear one Bio-Kil sock on one foot and a control sock on the other for four hours, and then they were told to exchange socks from one foot to the other for four hours. The socks were sampled and diluted and then inoculated to record bacterial counts. Bacterial counts were reduced in Bio-Kil socks compared with control socks in all S. aureus strains after 0 h, 8 h, and 48 h of incubation. In E. coli strains, bacterial counts declined in Bio-Kil socks comparing with control socks in most of the experiments with ESBL-negative E. coli and ATCC35218 at 0 h and 48 h of incubation. In all participants, the mean bacterial counts significantly decreased in Bio-Kil socks in comparison with control socks both at 0 h and at 40 h of incubation (p=0.003 at 0 h and p=0.006 at 40 h). Bio-Kil socks from diabetic patients showed significantly lessened bacterial count at 40 h of incubation (p=0.003). In healthy individuals, Bio-Kil socks reflected a significantly smaller mean bacterial count than control socks (p=0.016). Socks using Bio-Kil nanotechnology efficiently reduce bacterial counts in both diabetic patients and healthy individuals and might exert stronger efficacy in Gram-positive bacteria.